2004
DOI: 10.1080/02701367.2004.10609130
|View full text |Cite
|
Sign up to set email alerts
|

Neuromuscular Characteristics of Endurance- and Power-Trained Athletes

Abstract: In response to chronic physical training, the human neuromuscular system undergoes significant and specific adaptations. More importantly, these influences are the result of the type and quantity of physical activity. One of the simplest neuromuscular mechanisms is the spinal stretch reflex. The reflex system was previously viewed as inflexible, with a relatively fixed response that could vary only slightly. However, more recent data have identified an adaptive plasticity in the reflex system. In this respect,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0

Year Published

2009
2009
2023
2023

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 29 publications
(14 citation statements)
references
References 35 publications
0
14
0
Order By: Relevance
“…Because these fibers are involved in regulation of sensorimotor loop, muscle pain sensation and EPR, and in physiological adjustments ( Mitchell et al, 1977 ; Mazzone and Geraghty, 1999 ; Coull et al, 2003 ; Decherchi and Dousset, 2003 ; Edwards et al, 2003 ; Decherchi et al, 2004 , 2007 ; Cole et al, 2010 ), their alteration may be responsible of some troubles observed with aging during walking and running ( Markel et al, 2003 ; Houssiere et al, 2006 ), and at rest ( Ng et al, 1994 ; Markel et al, 2003 ). If a repeated exercise performed when adult does not seem to reverse the effects of aging on metabosensitive afferents, it has been proved that exercise induces many positive outputs on neuromuscular functions ( Koceja et al, 2004 ). In the future, it would be interesting to compare the type of exercise we have chosen in this study to others types of exercise or to animals that have been performed repeated exercises since they were young (i.e., throughout life).…”
Section: Discussionmentioning
confidence: 99%
“…Because these fibers are involved in regulation of sensorimotor loop, muscle pain sensation and EPR, and in physiological adjustments ( Mitchell et al, 1977 ; Mazzone and Geraghty, 1999 ; Coull et al, 2003 ; Decherchi and Dousset, 2003 ; Edwards et al, 2003 ; Decherchi et al, 2004 , 2007 ; Cole et al, 2010 ), their alteration may be responsible of some troubles observed with aging during walking and running ( Markel et al, 2003 ; Houssiere et al, 2006 ), and at rest ( Ng et al, 1994 ; Markel et al, 2003 ). If a repeated exercise performed when adult does not seem to reverse the effects of aging on metabosensitive afferents, it has been proved that exercise induces many positive outputs on neuromuscular functions ( Koceja et al, 2004 ). In the future, it would be interesting to compare the type of exercise we have chosen in this study to others types of exercise or to animals that have been performed repeated exercises since they were young (i.e., throughout life).…”
Section: Discussionmentioning
confidence: 99%
“…For example, there are increased cortical representations and MEP amplitudes to the involved muscles in highly skilled racquet players (Pearce et al 2000) and steeper IO curves in musicians (Rosenkranz et al 2007). Furthermore, examinations of spinal cord circuitry indicate that endurance‐trained individuals have enhanced H and stretch reflexes (see Koceja et al 2004 for a review), with increasing amplitude of H reflexes in more active individuals (Nielsen et al 1993). However, these changes in excitability have all been assessed in the muscle groups involved in the training, reflecting a likely task‐specific adaptation for the M1 representation of muscles in the exercising limb.…”
Section: Discussionmentioning
confidence: 99%
“…Intensive motor training induces task-specific changes in the excitability of spinal reflexes in people without injuries to the central nervous system [ 1 , 2 ]. For example, resistance training of the plantarflexor muscles over many weeks increases the excitability of the soleus (SOL) Hoffmann (H) reflex [ 3 , 4 ], whereas balance training on unstable surfaces for a few weeks does the opposite [ 5 7 ].…”
Section: Introductionmentioning
confidence: 99%